Kajian Pengaruh Perbedaan Rasio Penambahan Limbah Cair Pabrik Kelapa Sawit (LCPKS) terhadap Rasio C/N Kompos Tandan Kosong Kelapa Sawit (TKKS) dengan Penambahan Aktivator BAR Formula (Studi Kasus di PT Alamraya Kencana Mas, Kalimantan Selatan) - Ahdiat Leksi Siregar (JURNAL CITRA WIDYA EDUKASI, 2019)
This research porpose to determine the effect of the difference in the ratio of addition of Palm Oil Mill Liquid Waste (POMLW) to the C/N ratio of Palm Oil Empty Bunch (POEB) compost with the addition of formula BAR activator at PT Alamraya Kencana Mas, South Kalimantan Province. The method of data collection was conducted through interview with informants who knew the field of POEB composting, observation to the POEB composting area, and literature review in the form of a daily report on the composting process. Based on the study conducted, it was concluded that composting of POEB ﬁber by the addition of POMLW and Formula BAR activators took 45 days with the process stages, namely: 1) POEB stacking; 2) watering with POMLW; 3) inoculation with activator BAR Formula; 4) reversal with excavator; 5) milling with macerator; and 6) harvesting. The difference in the ratio of POMLW addition has a significant effect on compost maturity as indicated by the C/N ratio.